In situ polymerized hybrid polymer electrolytes for high voltage lithium batteries

In situ polymerization of unsaturated cyclic carbonate monomers and crosslinkers in lithium-ion batteries creates a hybrid electrolyte with improved ionic conductivity and stability, addressing the limitations of traditional electrolytes for high-energy applications.

JP7666787B2Active Publication Date: 2025-04-22EVONIK OPERATIONS GMBH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022549493
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-02-18
Publication Date
2025-04-22
Estimated Expiration
2040-02-18

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries face issues with anode stability, flammability, and poor compatibility with high-voltage cathodes due to the use of organic liquid electrolytes, while PEO-based solid polymer electrolytes suffer from low ionic conductivity and poor wettability, making them unsuitable for high-energy lithium batteries.

Method used

Development of a novel hybrid solid/gel polymer electrolyte through in situ polymerization using unsaturated cyclic carbonate monomers and multifunctional ester-based crosslinkers, such as vinyl ethylene carbonate (VEC) and trimethylolpropane ethoxylate triacrylate (ETPTA), which form superior polymer backbones with enhanced ionic conductivity, electrochemical stability, and flexibility.

Benefits of technology

The new polymer electrolytes exhibit higher ionic conductivity, wider electrochemical stability windows, and improved cycling performance compared to conventional electrolytes, enabling safer and more flexible lithium-ion batteries with suppressed lithium dendrite formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666787000009
    Figure 0007666787000009
  • Figure 0007666787000010
    Figure 0007666787000010
  • Figure 0007666787000011
    Figure 0007666787000011
Patent Text Reader

Abstract

A monomer material for preparing a polymer electrolyte precursor composition capable of forming an in-situ polymerized polymer electrolyte, the monomer material comprising, consisting essentially of, or consisting of A1) a first monomer and, optionally, A2) a second monomer. Also provided are a polymer electrolyte precursor raw material composition, a polymer electrolyte precursor composition capable of forming a polymer electrolyte comprising the monomer material, a polymer electrolyte, and an electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the preparation and development of in-situ hybrid polymer electrolytes for high voltage lithium metal batteries. [Background technology]

[0002] Due to the development and demand of various energy storage devices and systems, especially for electric vehicles, traditional lithium-ion batteries can no longer meet the needs of the market, and high energy / power density lithium batteries are urgently needed. -1 ), high voltage "LiNiCoyMn 1-x-y (4.3V or more vs.Li+ / Li, 150mAh g -1 Lithium batteries using "Li-ion batteries" (or more) are generally recognized as the next generation lithium battery. As one of the most important parts of a lithium battery other than the electrodes, the electrolyte also plays a vital role in state-of-the-art lithium batteries. Unfortunately, the anode stability of traditional organic liquid electrolytes using carbonate or ether-based solvents is lower than 4.V vs.Li / Li+ and is extremely unstable against new high voltage cathodes. In addition, commercial electrolytes contain many volatile and flammable organic components. Therefore, polymer electrolytes, especially solid polymer electrolytes (SPEs), have attracted more and more attention due to their reduced safety risk, high anode stability, and ability to suppress lithium dendrites.

[0003] PEO-based electrolytes are the most commonly studied among various known polymers, and their structure includes oligoethers (-CH2-CH2-O-)n, which can effectively dissolve Li salts. + The transport motive of is due to the flexible ethylene oxide segments and ether oxygen atoms. PEO-based electrolytes have low ionic conductivity due to their high crystallinity, and ion aggregation phenomenon often exists. Another problem with PEO-based electrolytes is their poor antioxidant ability (most of them are <4.2V vs.Li / Li +), which means that matching with high-voltage cathodes is nearly impossible. Furthermore, ex-situ PEO-based polymer electrolytes have poor wettability with the cathode, which can seriously affect the cycling performance.

[0004] Unlike conventional ex-situ PEO-based SPEs, in-situ polymerized SPEs are thermally prepared by a precursor solution consisting of a lithium salt, a polymerizable monomer, and a thermal initiator. In addition, the in-situ polymerized SPEs have good wettability with the cathode, which enables better cycle performance. Non-Patent Document 1 reports that an in-situ polymerized polyvinylene carbonate (PVCA)-based solid polymer electrolyte is prepared by the addition of LiCoO 2 / In Li batteries, Li / Li + Electrochemical stability window of up to 4.5 V and 9.82 × 10 at 50 °C -5 S cm -1 It was revealed that LiCoO 2 / The Li battery has a capacity of about 97mAh g at a current density of 0.1C. -1 However, this was due to the low ionic conductivity of PVCA-SPE and the large polarization at 25°C and 30°C. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] J. Chai et al. (J. Chai et al. Advance Science, Vol. 4 (2016), pp. 1600377) Summary of the Invention [Problem to be solved by the invention]

[0006] Therefore, it is an object of the present invention to develop a novel hybrid solid / gel polymer electrolyte by in situ polymerization. [Means for solving the problem]

[0007] The inventors surprisingly found that monomeric materials such as unsaturated cyclic carbonate monomers with carbon-carbon double bonds in the side chains and, in some cases, multifunctional ester-based crosslinkers such as ETPTA, could form excellent polymer backbones for solid or gel-like polymer electrolytes after in situ polymerization. Such polymer electrolytes exhibit superior performance in terms of cycling performance and electrochemical stability window compared to commercial liquid electrolytes. The obtained polymer electrolytes also exhibited higher ionic conductivity at room temperature compared to conventional PEO-based electrolytes and compact PVCA-based electrolytes. The obtained polymer electrolytes further exhibited better flexibility than PVCA solid polymer electrolytes, which could be used to create more flexible lithium-ion batteries. [Brief description of the drawings]

[0008] [Figure 1] 1 is a graph showing the ionic conductivity of the polymer electrolyte prepared in Example 1a. [Diagram 2] 1 is a graph showing the electrochemical stability window test results of the polymer electrolyte prepared in Example 1a. FIG. [Diagram 3] 3 shows the cycle performance of the electrolyte prepared at 0.2C rate using Li-NCM523 (FIG. 3a) as the cathode in Example 1a and Li-LiFPO4 (FIG. 3b) as the cathode in Example 1b. [Figure 4] 2 is a graph showing infrared test results demonstrating that VEC and ETPTA were completely reacted according to Example 2-1a. [Diagram 5] 1 is a graph showing the ionic conductivity of the polymer electrolytes prepared in Example 2-1a, Example 2-2, and Example 2-3. [Figure 6] 6 is a graph showing the results of electrochemical stability window tests of the polymer electrolytes prepared in Example 2-1a (FIG. 6a), Example 2-2 (FIG. 6b), and Example 2-3 (FIG. 6c). [Figure 7]FIG. 7 shows the cycle performance of polymer electrolytes at 0.2C rate when NCM523 is used as the cathode in Example 2-1a (FIG. 7a), Example 2-2 (FIG. 7b), and Example 2-3 (FIG. 7c), and when LiFePO4 is used as the cathode in Example 2-1b (FIG. 7d). [Figure 8] 1 is a graph showing the ionic conductivity (conductivity) of the polymer electrolytes prepared in Examples 3-1, 3-2, 3-3a, and 3-4. [Figure 9] 9 is a graph showing the results of electrochemical stability window tests of the polymer electrolytes prepared in Example 3-1 (FIG. 9a), Example 3-2 (FIG. 9b), Example 3-3a (FIG. 9c), and Example 3-4 (FIG. 9d). [Figure 10] 10 is a graph showing the cycle performance of the polymer electrolytes prepared in Example 3-1 (FIG. 10a), Example 3-2 (FIG. 10b), Example 3-3a (FIG. 10c), and Example 3-4 (FIG. 10d) at a rate of 0.5C, using NCM523 as a cathode and LiFe10PO4 as a cathode. [Figure 11] 11A is a graph showing the electrochemical stability window (FIG. 11a) and cycle performance (FIG. 11b) of the Li-NCM523 battery prepared in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention relates to a monomer material (i.e., a monomer composition) for preparing a polymer electrolyte precursor composition capable of forming an in-situ polymer electrolyte, comprising: A1) Formula (I):

[0010] [ka] (wherein R represents H, F, methyl or ethyl; m represents 0, 1, 2 or 3). more preferably vinyl ethylene carbonate (VEC); and A2) Formula (II):

[0011] [ka] (Wherein, R is methyl, - CH2OH, ethyl, or - CH2CH2OH, preferably R is methyl, - CHOH, or ethyl; a, b, and c each independently represent 0, 1, 2, or 3, and a+b+c≧2, preferably a+b+c≧3. a second monomer represented by the formula: The present invention provides a monomeric material comprising, consisting essentially of, or consisting of: The first monomer represented by formula (I) is an unsaturated cyclic carbonate monomer having a carbon-carbon double bond in the side chain. The monomeric materials can be used to prepare a polymer electrolyte precursor composition, which can then be used to form an in situ polymerized polymer electrolyte. In some examples, the mass ratio of the first monomer to the second monomer is preferably from 9.5:0.5 to 5:5, more preferably from 9.5:0.5 to 8:2, and even more preferably from 9:1 to 8:2.

[0012] The second monomer can function as a cross-linking agent. The use of the second monomer in the monomer material helps to obtain a higher electrochemical stability window. However, the addition of a cross-linking agent to the monomer material reduces the ionic conductivity of the polymer electrolyte. If the monomer material contains too much of the second monomer, the gel polymer electrolyte prepared will have low ionic conductivity.

[0013] The present invention further provides a polymer electrolyte precursor raw material composition for preparing a polymer electrolyte precursor composition capable of forming an in situ polymerized polymer electrolyte, the composition comprising: A) a monomeric material as claimed in claim 1; and B) a free radical initiator for the thermal polymerization reaction of said monomeric material; The polymer electrolyte precursor material composition comprises, consists essentially of, or consists of:

[0014] The present invention further provides a polymer electrolyte precursor composition capable of forming an in situ polymerized polymer electrolyte, comprising: A) a monomeric material as claimed in claim 1; B) a free radical initiator for the thermal polymerization reaction of said monomeric material; C) a lithium salt, preferably lithium bis(fluorosulfonyl)imide; and D) Optionally, an organic solvent, preferably a carbonate solvent, more preferably ethylene carbonate / dimethyl carbonate. A polyelectrolyte precursor composition comprising, consisting essentially of, or consisting of: The mass ratio of the monomer material to the organic solvent is 1:0 to 1:0.5, preferably 1:0.1 to 1:0.3, and more preferably 1:0.2 to 1:0.3. The amount of the monomer material relative to the total mass of the polymer electrolyte precursor composition is 50 to 95 mass%, for example, 60 to 80 mass%, preferably 70 to 80 mass%, and more preferably 75 to 80 mass%. The method for preparing the polymer electrolyte precursor composition capable of forming the in situ polymerized polymer electrolyte of the present invention may be a conventional method, for example a method comprising mixing the components of the polymer electrolyte precursor composition.

[0015] The present invention further provides a method for in-situ preparation of a polyelectrolyte, comprising: 1) injecting the polymer electrolyte precursor composition according to claim 3 into a battery case equipped with an electrode assembly and then sealing the battery case; and 2) heating the polyelectrolyte precursor composition to polymerize it in situ; A method is provided, comprising the steps of:

[0016] In one embodiment, the polymerization reaction of the first monomer is as follows:

[0017] [ka] This can be shown diagrammatically as follows. In another embodiment, the reaction of the first monomer with the second monomer is as follows:

[0018] [ka] This can be shown diagrammatically as follows.

[0019] The present invention further provides polymer electrolytes, particularly gel or solid polymer electrolytes, formed by (polymerization of) a polymer electrolyte precursor composition comprising a monomeric material of the present invention or prepared according to the method of the present invention. The present invention further provides a polymer electrolyte for a secondary battery comprising a polymer that is the reaction product of a monomer material of the present invention and a free radical initiator.

[0020] The present invention further provides the following: (i) a polymer that is the reaction product of a monomeric material of the present invention and a free radical initiator; and (ii) an organic solvent containing an amount of an ionic salt effective to achieve an ionic conductivity of about 0.46 mS / cm or less; The present invention provides a polymer electrolyte for a secondary battery, comprising: In some examples, the ionic salt is a lithium salt. The present invention further provides a polyelectrolyte prepared in situ by the polyelectrolyte precursor composition according to the present invention. The polyelectrolyte can be prepared according to the methods of the prior art.

[0021] The present invention further provides a secondary battery comprising an anode, a cathode, a microporous separator separating the anode and the cathode, and the polymer electrolyte of the present invention.

[0022] The present invention further provides a lithium ion battery comprising a polymer electrolyte prepared in situ by (polymerization) of a polymer electrolyte precursor composition according to the present invention. The present invention further provides an electrochemical device comprising a polymer electrolyte according to the present invention. In some examples, the electrochemical device is a secondary battery.

[0023] The present invention further comprises the following: Preparing a battery case comprising an electrode assembly; Injecting the polymer electrolyte precursor composition according to claim 3 into the battery case and then sealing it; and polymerizing the polyelectrolyte precursor composition; The present invention provides a device manufactured by a process comprising: The polymerization may be a thermal polymerization.

[0024] The polymer electrolyte of the present invention may be in a gel state (i.e., a gel-like polymer electrolyte) or in a solid state (i.e., a solid polymer electrolyte), and preferably, the polymer electrolyte is in a gel state. The polymer electrolyte precursor composition of the present invention can prepare the polymer electrolyte in a gel state or a solid state depending on the amount of the organic solvent in the polymer electrolyte precursor composition. For example, as shown in Examples 1 and 2, when the polymer electrolyte precursor composition does not contain an organic solvent, the obtained polymer electrolyte is in a solid state. When the polymer electrolyte precursor composition contains an organic solvent as in Example 3, the obtained polymer electrolyte is in a gel state. The type of lithium ion battery in which the electrolyte of the present invention can be used is not particularly limited. In some examples, the lithium ion battery is a LMB.

[0025] In some examples, the present invention provides a method for producing a method for the treatment of a variety of conditions comprising the steps of: A) A monomeric material consisting of vinyl ethylene carbonate and trimethylolpropane ethoxylate triacrylate; B) free radical initiators; C) Lithium salts, such as lithium bis(fluorosulfonyl)imide; and D) an organic solvent, preferably a carbonate solvent such as ethylene carbonate / dimethyl carbonate; A polymer electrolyte precursor composition capable of forming a polymer electrolyte comprising, consisting essentially of, or consisting of: The mass ratio of the vinyl carbonate to the trimethylolpropane ethoxylate triacrylate is 9.5:0.5 to 5:5, preferably 9.5:0.5 to 8:2, more preferably 9:1 to 8:2; Here, the mass ratio of the monomer material to the organic solvent is 1:0 to 1:0.5, preferably 1:0.1 to 1:0.3, and more preferably 1:0.2 to 1:0.3, wherein The amount of the monomer material relative to the total mass of the polymer electrolyte precursor composition is 50 to 95 mass%, preferably 75 to 80 mass%. A polyelectrolyte precursor composition is provided. The amount of lithium bis(fluorosulfonyl)imide relative to the total mass of the polymer electrolyte precursor composition is preferably about 15 mass %.

[0026] The present invention further provides the use of the monomer material of the present invention, or the polymer electrolyte precursor raw material composition of the present invention, or the polymer electrolyte precursor composition of the present invention in the preparation of an in situ polymerized polymer electrolyte or an electrochemical device.

[0027] Those skilled in the art can determine a suitable separator for a lithium-ion battery using the polymer electrolyte of the present invention. For example, the separator may be surface-modified or not, may have a thickness of less than 20 μm or less than 30 μm, may have a porosity of more than 70% or 80%, and may be made of, for example, cellulose or polytetrafluoroethylene (PTFE).

[0028] First Monomer In some examples, the carbonate ester monomer is preferably vinyl ethylene carbonate (VEC), having the chemical formula: C5H6O3, CAS Login Number: 4427-96-7.

[0029] Second Monomer The second monomer is preferably trimethylolpropane ethoxylate triacrylate (ETPTA) or other monomers having a similar molecular structure to ETPTA, such as trimethylolpropane triacrylate (TMPTA), pentaerythritol triacrylate (PETA), etc. Trimethylolpropane ethoxylate triacrylate (ETPTA) has an average Mn of about 428 and a CAS login number of 28961-43-5.

[0030] Free Radical Initiators The free radical initiator for the polymerization reaction of the monomers may be any of those conventionally used in the art for the thermal polymerization reaction of the monomers. Examples of free radical initiators and polymerization initiators include azo compounds such as 2,2-azobis(2-cyanobutane), 2,2-azobis(methylbutyronitrile), 2,2'-azoisobutyronitrile (AIBN), and azobisdimethyl-valeronitrile (AMVN), peroxy compounds such as benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, cumyl peroxide, and hydrogen peroxide, and hydroperoxides. In addition, AIBN, 2,2'-azobis(2,4-dimethylvaleronitrile) (V65), and di-(4-tert-butylcyclohexyl)-peroxydicarbonate (DBC), etc. are preferably used. Preferably, the free radical initiator may be selected from azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), benzoyl peroxide (BPO), lauroyl peroxide (LPO), etc. More preferably, the free radical initiator is azobisisobutyronitrile (AIBN).

[0031] The amount of the free radical initiator may be a conventional amount, and the amount of the free radical initiator relative to the total mass of the polymer electrolyte precursor composition may be preferably 0.1 to 3 mass %, more preferably about 0.5 mass %.

[0032] The polymerization initiator is decomposed at a predetermined temperature of 40 to 80°C to generate radicals, which can react with the monomers through free radical polymerization to form a gel-like polymer electrolyte. In general, free radical polymerization is carried out by a sequence of reactions consisting of an initiation reaction involving the formation of a temporary molecule with high reactivity or active sites, a propagation reaction involving the reformation of active sites at the chain ends by the addition of monomers to the active chain ends, a chain transfer reaction involving the transfer of active sites to other molecules, and a termination reaction involving the destruction of the active chain center.

[0033] Lithium salts The lithium salt is a substance that dissolves in the non-aqueous electrolyte to cause dissociation of lithium ions. The lithium salt may be any commonly used in the art, but is thermally stable during in situ polymerization (e.g., at 80° C.), and non-limiting examples include lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalatoborate (LiODFB), LiAsF, LiClO, LiN(CFSO), LiBF, LiSbF, and LiCl, LiBr, LiI, LiB 10 Cl 10 At least one selected from the group consisting of LiCF3SO3, LiCF3CO2, LiAlCl4, CH3SO3Li, CF3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate, and imide. The lithium salt is preferably selected from LiFSI, LiTFSI, and LiODFB. These materials may be used alone or in combination. The amount of the lithium salt relative to the total mass of the polymer electrolyte precursor composition may be a conventional amount, for example, 5 to 40 mass %, and is most preferably about 15 mass %.

[0034] Organic solvents The organic solvent may be, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidinone, propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, dimethyl sulfoxide, methyl formate, methyl acetate, phosphoric acid triester, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, methyl propionate, ethyl propionate, etc. These materials may be used alone or in combination. The organic solvent is preferably a carbonate solvent. The carbonate solvent is preferably selected from the group consisting of ethylene carbonate / dimethyl carbonate (EC / DMC), ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and gamma-butyrolactone (GBL). In some examples, the organic solvent is preferably ethylene carbonate / dimethyl carbonate (EC / DMC, EC / DMC=50 / 50 (v / v)).

[0035] As long as the polymer electrolyte is in a gel state, the amount of the organic solvent may be a conventional amount. For example, if the amount of the organic solvent is too large and the mass ratio of the monomer material to the organic solvent is less than 1:0.5, a good gel state may not be formed.

[0036] In order to improve the charge / discharge characteristics and flame retardancy, for example, pyridine, triethyl phosphite, triethanolamine, ethylenediamine, n-glyme, hexaphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. may be added to the electrolyte. In some cases, in order to impart non-flammability, the electrolyte may further contain a halogen-containing solvent such as carbon tetrachloride or ethylene trifluoride.

[0037] The electrochemical device includes any type of device that causes an electrochemical reaction. Examples of the electrochemical device include any type of primary battery, secondary battery, fuel cell, solar cell, capacitor, etc., and preferably, secondary battery. In general, a secondary battery is produced by incorporating an electrolyte into an electrode assembly that is composed of a cathode and an anode that face each other with a separator therebetween. The cathode is manufactured, for example, by applying a mixture of the cathode active material, the conductive material, and the binder to a cathode current collector, followed by drying and pressing. If necessary, a filler may be added to the mixture.

[0038] Examples of cathode active materials that can be used in the present invention include layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or LiNiCoMn 1-x-y (NCM)” and other transition metal-substituted compounds of the formula “Li 1+x Mn 2-x O4" (0≦x≦0.33), lithium manganese oxides such as compounds of "LiMnO3", "LiMn2O3", and "LiMnO2"; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, and Cu2V2O7; 1-x M x O2" (M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, 0.01≦x≦0.3); 2-x M x O2" (M=Co, Ni, Fe, Cr, Zn or Ta, 0.01≦x≦0.1) or formula 「 Li2Mn3MO 8」 Examples include, but are not limited to, lithium manganese composite oxides (M=Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li is substituted with an alkaline earth metal ion; disulfide compounds; Fe2(MoO4)3, LiFe3O4, and the like. In some examples of the present invention, the cathode is "LiNi5Co2Mn3" and 「 "LiFe3O4" is used.

[0039] Because the polymer electrolytes of the present invention exhibit a high electrochemical stability window (>5V), the polymer electrolytes are particularly useful for NCM cathodes. Examples of anode active materials that can be used in the present invention include non-graphitized carbon and graphitized carbon such as "LixFe2O3" (0≦x≦1), "LixWO2" (0≦x≦1), "LixWO2" (0≦x≦1), and "SnxMe 1-x Me' y O z " (Me: Mn, Fe, Pb or Ge; Me': Al, B, P, Si, Group I, II or III element of the periodic table, or halogen; 0≦x≦1; 1≦y≦3; and 1≦z≦8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5; conductive polymers such as polyacetylene; and Li-Co-Ni based materials. In some examples of the present invention, lithium metal is used as the anode.

[0040] The secondary battery according to the present invention may be, for example, a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, a lithium ion polymer secondary battery, etc. The secondary battery may be manufactured in various forms. For example, the electrode assembly may be configured as a jelly roll structure, a stack structure, a stack / fold structure, etc. The battery may have a configuration in which the electrode assembly is installed in a battery case that is a cylindrical can, a prismatic can, or a laminate sheet including a metal layer and a resin layer. Such battery configurations are widely known in the art.

[0041] Therefore, the present invention provides a novel polymer electrolyte by in situ polymerization of the polymer electrolyte precursor composition of the present invention. The polymer electrolyte can be prepared in situ, and the thickness of the electrolyte can be conveniently controlled. In addition, the monomers such as the first monomer and the second monomer form an excellent polymer backbone after polymerization, and show excellent cycle performance and high electrochemical stability window compared to commercial liquid electrolytes. In addition, the polymer electrolyte is less flammable, indicating that it is safer than conventional liquid electrolytes. In addition, when lithium metal is used as the anode, the formation of lithium dendrites can be suppressed due to the excellent mechanical properties of the electrolyte. In addition, the PVC-based polymer electrolyte does not react with the lithium foil during the polymerization process, compared to PVC. The electrolyte is also particularly suitable for use in LMBs, since it does not require the consumption of large amounts of solvents used in conventional lithium metal batteries. Compared to conventional PEO-based polymer electrolytes, the polymer electrolyte of the present invention showed excellent ionic conductivity, wide electrochemical window, and better cycle performance.

[0042] Furthermore, the monomeric materials of the present invention are chemically stable because the first monomer, particularly VEC, does not react with Li, which is an important advantage over monomeric materials containing vinylene carbonate (VC), which may back-react with Li as a side reaction. Other advantages of the present invention will be apparent to those skilled in the art upon reading the specification.

[0043] Fabrication of lithium metal batteries Lithium metal batteries include: a) preparation of an electrolyte precursor composition solution; and b) Assembly of lithium metal batteries and in situ polymerization by heating It is prepared by the method of Steps a) and b) were carried out in a glove box filled with argon gas (H2O, O2≦0.5 ppm). EXAMPLES

[0044] In order to describe the contents and effects of the present invention in detail, the present invention will be further described below in combination with examples, comparative examples and related drawings. Unless otherwise stated, all tests in the following examples were carried out at room temperature.

[0045] Example 1a (Li-NCM523) 1) Preparation of precursor electrolyte solution: 1 g of vinyl ethylene carbonate (VEC), 0.157 g of bis(fluorosulfonyl)lithium imide (LiFSI) and 3 mg of AIBN were mixed and stirred at 25° C. for 0.5 hours to obtain a precursor electrolyte solution. 2) Assembly of the battery by heating and in-situ polymerization: The "LiNi5Co2Mn3 (NCM523)" cathode was prepared as follows. NCM523, acetylene black, and poly(vinylidene difluoride) were mixed in a mass ratio of 80:10:10 to form a viscous slurry. The viscous slurry was then coated onto a flat carbon-coated aluminum foil by doctor blade method. The carbon-coated aluminum foil with the viscous slurry was dried in an air circulating oven at 70 °C for 1 h and further dried at 100 °C under high vacuum for 12 h to obtain the NCM523 cathode. The active material (LiNi5Co2Mn 3) The mass loading is 3-5 mg cm -2 The precursor electrolyte solution was injected into a 2032 lithium battery equipped with a cellulose separator separating the cathode and anode (Li foil), and the battery was heated at 80° C. for 24 hours. This heating process resulted in a solid polymer electrolyte without any mobile liquid phase between the cathode and anode, which was evident when the 2032 battery was disassembled.

[0046] Example 1b (Li-LFP) 1) Preparation of precursor electrolyte solution: 1 g of vinyl ethylene carbonate (VEC), 0.157 g of bis(fluorosulfonyl)lithium imide (LiFSI) and 3 mg of AIBN were mixed and stirred at 25° C. for 0.5 hours to obtain a precursor electrolyte solution. 2) Cell assembly by heating and in situ polymerization: The LiFePO4 (LFP) cathode was prepared as follows. LFP, acetylene black, and poly(vinylidene difluoride) were mixed in a mass ratio of 80:10:10 to form a viscous slurry. The viscous slurry was then coated onto a flat carbon-coated aluminum foil by doctor blade method. The carbon-coated aluminum foil with the viscous slurry was dried in an air circulating oven at 70°C for 1 hour and further dried under high vacuum at 100°C for 12 hours to obtain the LiFePO4 cathode. The active material (LiFePO 4) The mass loading is 3-5 mg cm -2 The precursor electrolyte solution was injected into a 2032 lithium battery equipped with a cellulose separator separating the cathode and anode (Li foil), and the battery was heated at 80° C. for 24 hours. This heating process resulted in a solid polymer electrolyte without any mobile liquid phase between the cathode and anode, which was evident when the 2032 battery was disassembled.

[0047] Example 2-1a (Li-NCM523) 1) Preparation of precursor electrolyte solution: 0.9 g of vinyl ethylene carbonate (VEC), 0.1 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 h to obtain a precursor electrolyte solution. 2) Battery assembly by heating and in-situ polymerization were carried out in a similar manner as in Example 1a. After the heating process, a solid polymer electrolyte without any flowable liquid phase between the cathode and the anode could be obtained, which could be confirmed when the 2032 battery was disassembled.

[0048] Example 2-1b (Li-LFP) 1) Preparation of precursor electrolyte solution: 0.9 g of vinyl ethylene carbonate (VEC), 0.1 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 hours to obtain a precursor electrolyte solution. 2) Battery assembly by heating and in-situ polymerization were carried out in a similar manner as in Example 1b. After the heating process, a solid polymer electrolyte without any flowable liquid phase between the cathode and the anode could be obtained, which could be confirmed when the 2032 battery was disassembled.

[0049] Example 2-2 1) Preparation of precursor electrolyte solution: 0.8 g of vinyl ethylene carbonate (VEC), 0.2 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 h to obtain a precursor electrolyte solution. 2) Battery assembly by heating and in-situ polymerization were carried out in a similar manner as in Example 1a. After the heating process, a solid polymer electrolyte without any flowable liquid phase between the cathode and the anode could be obtained, which could be confirmed when the 2032 battery was disassembled.

[0050] Example 2-3 1) Preparation of precursor electrolyte solution: 0.7 g of vinyl ethylene carbonate (VEC), 0.3 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 h to obtain a precursor electrolyte solution. 2) Battery assembly by heating and in-situ polymerization were carried out in a similar manner as in Example 1a. After the heating process, a solid polymer electrolyte without any flowable liquid phase between the cathode and the anode could be obtained, which could be confirmed when the 2032 battery was disassembled.

[0051] Example 3-1 1) Preparation of precursor electrolyte solution: 0.9 g of vinyl carbonate resin (VEC), 0.1 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.1 g of EC / DMC, 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 h to obtain a precursor electrolyte solution. 2) Battery assembly by heating and in-situ polymerization were carried out in a similar manner as in Example 1a. After the heating process, a gel-like polymer electrolyte without any fluid liquid phase between the anode and cathode was obtained, which could be confirmed when the 2032 battery was disassembled.

[0052] Example 3-2 1) Preparation of precursor electrolyte solution: 0.9 g of vinyl ethylene carbonate (VEC), 0.1 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.2 g of EC / DMC, 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 h to obtain a precursor electrolyte solution. 2) Battery assembly by heating and in-situ polymerization were carried out in a similar manner as in Example 1a. After the heating process, a gel-like polymer electrolyte without any fluid liquid phase between the anode and cathode was obtained, which could be confirmed when the 2032 battery was disassembled.

[0053] Example 3-3a (Li-NCM523) 1) Preparation of precursor electrolyte solution: 0.9 g of vinyl ethylene carbonate (VEC), 0.1 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.3 g of EC / DMC, 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 h to obtain a precursor electrolyte solution. 2) Battery assembly by heating and in-situ polymerization were carried out in a similar manner as in Example 1a. After the heating process, a gel-like polymer electrolyte without any fluid liquid phase between the anode and cathode was obtained, which could be confirmed when the 2032 battery was disassembled.

[0054] Example 3-3b (Li-LFP) 1) Preparation of precursor electrolyte solution: 0.9 g of vinyl ethylene carbonate (VEC), 0.1 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.3 g of EC / DMC, 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 h to obtain a precursor electrolyte solution. 2) The battery assembly and in-situ polymerization by heating were carried out in the same manner as in Example 1b. After the heating process, a gel-like polymer electrolyte without any fluid liquid phase between the anode and cathode was obtained, which could be confirmed when the 2032 battery was disassembled.

[0055] Examples 3-4 1) Preparation of precursor electrolyte solution: 0.9 g of vinyl carbonate resin (VEC), 0.1 g of trimethylolpropane ethoxylate triacrylate (ETPTA average Mn ~ 428), 0.4 g of EC / DMC, 0.157 g of LiFSI and 3 mg of AIBN were mixed and stirred at 25 °C for 0.5 h to obtain a precursor electrolyte solution. 2) Battery assembly by heating and in-situ polymerization were carried out in a similar manner as in Example 1a. After the heating process, a gel-like polymer electrolyte without any fluid liquid phase between the anode and cathode was obtained, which could be confirmed when the 2032 battery was disassembled.

[0056] Comparative Example 1 Battery Assembly: A 2032 lithium battery with a polypropylene (PP) separator separating the cathode and anode as in Example 1a was filled with a commercial liquid electrolyte of 1M LiPF6 in EC / DMC (v / v 1 / 1).

[0057] Characterization of polyelectrolyte structure Furthermore, the chemical structure of the solid polymer electrolyte prepared in Example 2-1a was analyzed using Fourier transform infrared spectroscopy (FTIR). As can be seen from FIG. 4, after polymerization, the terminal double bond hydrogen (-C=CH 2) 2900cm -1 , 2950 cm -1 and 915-905cm for the -C=C- group. -1 , 995-985cm -1 The absorption peak disappears, which corresponds well to the change in chemical structure of the C=C double bond to a C-C single bond.

[0058] Performance Testing 1. Electrolyte cycling performance The cycling performance of the batteries was evaluated at room temperature using a LAND battery test system (Wuhan Kingfish Electronics Co., Ltd., China) with LiNi5Co2Mn3 or LiFePO4 as cathode and Li metal as anode. The cut-off voltages were 4.3V / 4.2V for Li / Li+ during charging (Li extraction) and 2.7V / 2.4V for Li / Li+ during discharging (Li insertion). All the batteries involved were activated by a small current before cycling. The C rate for all electrochemical measurements was 1C=160mA g -1 The test results are shown in Figures 3, 7, 10, and 11. In each figure, the solid dots represent the discharge capacity and the hollow dots represent the coulombic efficiency.

[0059] 11, the cells were evaluated at a 0.2 C rate. The cell of Comparative Example 1 achieved high discharge capacity in the first few cycles, but this capacity declined rapidly after 200 cycles with a capacity retention of 64.1%, and the coulombic efficiency of the electrolyte of Comparative Example 1 was >99%.

[0060] In Figures 3 and 7, the batteries were evaluated at a 0.2C rate. The cycle performance of the solid polymer electrolytes of Examples 1 and 2-(1-3) showed obviously better cycle performance because the discharge capacity did not obviously decrease as in Comparative Example 1, and the capacity retention after 200 cycles of Example 1a and Example 2-(1-3) was 78.9%, 80.5%, 73.5%, and 70.2%, respectively, when NCM523 was used as the cathode, and the capacity retention of Example 1b in Figure 3 and Example 2-1b in Figure 7, respectively, when LiFePO4 was used as the cathode, was 85.5% and 86.8%. The coulombic efficiency of all the batteries shown in Table 1 was 99% or more, which indicates that the cycle performance of the solid polymer electrolytes prepared in Examples 1 and 2-(1-3) of the present invention has a significantly beneficial effect.

[0061] In Figure 10, the battery was evaluated at a 0.5C rate. The cycling performance of the gelled polymer electrolyte of Example 3-(1-4) achieved high discharge capacity due to its higher ionic conductivity than the solid. The capacity retention after 200 cycles of Example 3-(1-4) was 73.2%, 79.0%, 85.4%, and 77.1% when NCM 523 was used as the cathode, respectively, and the capacity retention of Example 3-3b in Figure 10 when LiFePO4 was used as the cathode was 89.7%.

[0062] [Table 1] However, batteries containing all solid polymer electrolytes have had low specific capacities due to their lower ionic conductivity than gel-type polymer or liquid electrolytes.

[0063] 2. Electrochemical stability window The electrochemical stability of the polymer electrolyte of the present invention and the liquid electrolyte of Comparative Example 1 was evaluated using a CHI760e electrochemical workstation (Shanghai Chenghua Instruments Co., Ltd.) at room temperature with a scan rate of 10 mV vs. Li+ / Li from the open circuit voltage of each cell to 6 V. S-1The results were evaluated by linear sweep voltammetry (LSV) using a SS (stainless steel) / gelled polymer electrolyte (GPE) / Li coin cell at 300°C. The results are shown in Figures 2, 6, 9, and 11.

[0064] 2, 6, and 9 show the electrochemical stability window of the polymer electrolyte, and FIG. 11 shows the electrochemical stability window of the liquid electrolyte. The liquid electrolyte of Comparative Example 1 shows an electrochemical stability window of about 4.6 V, and it is clear that the polymer electrolyte has a higher electrochemical stability window than the liquid electrolyte. The electrochemical stability window of the polymer electrolyte according to the present invention is more stable, for example, Example 1a (4.8 V), Example 2-(1-3) (5.2 V), and Example 3-(1-4) (5 V), which contributes to better electrochemical performance. The extremely stable electrochemical stability window of about 5 V or more is very important, which allows the battery to use new high nickel content cathodes.

[0065] 3.Ionic conductivity AC impedance spectroscopy was measured on a CHI760e electrochemical workstation. The ionic conductivity of the polymer electrolyte was measured in a SS / GPE / SS cell with an applied voltage of 5 mV, and the results are shown in Figures 1, 5, and 8. The ionic conductivity (conductivity) of the electrolytes of different examples was calculated based on Figures 1, 5, and 8, and summarized in Table 2 below.

[0066] [Table 2] Ionic conductivity at room temperature is 1.95×10 -5 The ionic conductivity of the solid polymer electrolyte of the present invention (6.96×10 in Example 1a) is higher than that of the PVCA solid polymer electrolyte disclosed by J. Chai et al. (J. Chai et al. Advance Science, Vol. 4 (2016), pp. 1600377), which disclosed a PVCA solid polymer electrolyte of 1.0 S / cm. -5 S / cm ) is high. In addition, the ionic conductivity is about 2.1×10 ―6This is much higher than traditional PEO-based solid polymer electrolytes, which can only provide extremely low ionic conductivity of 1.2 S / cm (K. Wen et al. J. Mater. Chem. A, Vol. 6 (2018), pp11631-11663).

[0067] As used herein, terms such as "comprise(s)" are open terms meaning "including at least," unless otherwise specified. All references, tests, standards, documents, publications, etc. mentioned herein are incorporated by reference. When numerical limitations or ranges are listed, the endpoints are included. Also, all values ​​and subranges within the numerical limitations or ranges are specifically included as if expressly written out. The above description is presented to enable any person skilled in the art to make and use the invention, and is provided in the context of a particular application and its requirements. Various modifications to the preferred embodiment will be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the invention. Thus, the present invention is not intended to be limited to the embodiments shown, but is to be accorded the widest scope consistent with the principles and features disclosed herein. In this regard, a particular embodiment within the invention may not represent all of the benefits of the invention broadly considered.

Claims

1. A monomeric material for preparing a polymer electrolyte precursor composition capable of forming an in-situ polymer electrolyte, comprising: A1) A compound represented by the following formula (I): 【Chemistry 1】 (wherein R represents H, F, methyl or ethyl; m represents 0, 1, 2, or 3). A first monomer represented by: A2) A compound of the following formula (II): 【Chemistry 2】 (Wherein R is methyl, - CH 2 OH, ethyl, or - CH 2 CH 2 OH; a, b, and c each independently represent 0, 1, 2, or 3, and a+b+c≧2. A second monomer represented by: A monomer material consisting of: The mass ratio of the first monomer to the second monomer is 9.5:0.5 to 5:5; Monomeric materials.

2. 1. A polymer electrolyte precursor raw material composition for preparing a polymer electrolyte precursor composition capable of forming an in situ polymerized polymer electrolyte, comprising: A) the monomeric material of claim 1; and B) a free radical initiator for the thermal polymerization reaction of said monomeric material; The polymer electrolyte precursor raw material composition comprises:

3. The in situ polymerized polyelectrolytes can be formed as follows: A) the monomer material of claim 1; B) a free radical initiator for the thermal polymerization reaction of said monomeric material; C) a lithium salt; and D) Organic Solvent A polymer electrolyte precursor composition comprising: the weight ratio of the monomer material to the organic solvent is 1:0 to 1:0.5;

4. The polymer electrolyte precursor composition according to claim 3, wherein the amount of the monomer material relative to the total weight of the polymer electrolyte precursor composition is 50 to 95% by weight.

5. 1. A method for in-situ preparation of a polyelectrolyte, comprising: 1) injecting the polymer electrolyte precursor composition according to claim 3 into a battery case equipped with an electrode assembly, and then sealing the battery case; and 2) heating the polymer electrolyte precursor composition to polymerize it in situ; A method comprising:

6. 10. A polymer electrolyte formed by the polymer electrolyte precursor composition of claim 3 or prepared by the method of claim 5.

7. 10. A polymer electrolyte for a secondary battery comprising a polymer which is the reaction product of the monomer material of claim 1 and a free radical initiator.

8. below: (i) a polymer that is the reaction product of the monomeric material of claim 1 and a free radical initiator; and (ii) an organic solvent containing an amount of an ionic salt effective to achieve an ionic conductivity of 0.46 mS / cm or less; A polymer electrolyte for a secondary battery comprising:

9. A secondary battery comprising an anode, a cathode, a microporous separator separating the anode and the cathode, and the polymer electrolyte according to any one of claims 6 to 8.

10. A lithium ion battery comprising a polymer electrolyte prepared in situ from the polymer electrolyte precursor composition of claim 3.

11. An electrochemical device comprising the polymer electrolyte according to any one of claims 6 to 8.

12. below, A) a monomeric material consisting of vinyl ethylene carbonate and trimethylolpropane ethoxylate triacrylate; B) a free radical initiator; C) a lithium salt; and D) an organic solvent; A polymer electrolyte precursor composition capable of forming a polymer electrolyte consisting of: The mass ratio of the vinylethylene carbonate to the trimethylolpropane ethoxylate triacrylate is 9.5:0.5 to 5:5; wherein the mass ratio of the monomer material to the organic solvent is 1:0 to 1:0.5; the amount of the monomer material relative to the total weight of the polymer electrolyte precursor composition is 50 to 95% by weight; Polyelectrolyte precursor composition.

13. Use of the monomer material according to claim 1, or the polymer electrolyte precursor raw material composition according to claim 2, or the polymer electrolyte precursor composition according to claim 3 in the preparation of an in situ polymerized polymer electrolyte or an electrochemical device.

14. 2. The monomer material of claim 1, wherein the first monomer is vinyl ethylene carbonate.

15. 2. The monomer material of claim 1, wherein the second monomer is trimethylolpropane ethoxylate triacrylate.

16. 2. The monomeric material of claim 1, wherein a+b+c>3.

17. 2. The monomer material according to claim 1, wherein a mass ratio of the first monomer to the second monomer is from 9.5:0.5 to 8:2, or from 9:1 to 8:

2.

18. In formula (II), R is methyl; - CH 2 2. The monomeric material of claim 1, wherein the aryl group is OH or ethyl.

19. 13. The polymer electrolyte precursor composition of claim 3 or 12, wherein the lithium salt is lithium bis(fluorosulfonyl)imide.

20. 13. The polymer electrolyte precursor composition of claim 3 or 12, wherein the organic solvent is a carbonate solvent or ethylene carbonate / dimethyl carbonate.

21. The polymer electrolyte precursor composition according to claim 3 or 12, wherein a mass ratio of the monomer material to the organic solvent is from 1:0.1 to 1:0.3, or from 1:0.2 to 1:0.

3.

22. The polymer electrolyte precursor composition according to claim 3, wherein the amount of the monomeric material relative to the total weight of the polymer electrolyte precursor composition is 60 to 80% by weight or 75 to 80% by weight.

23. The polymer electrolyte precursor composition according to claim 12, wherein a mass ratio of the vinyl ethylene carbonate to the trimethylolpropane ethoxylate triacrylate is 9.5:0.5 to 8:2 or 9:1 to 8:

2.

24. The polymer electrolyte precursor composition according to claim 12, wherein the amount of the monomeric material is 75 to 80% by weight based on the total weight of the polymer electrolyte precursor composition.

Citation Information

Patent Citations

  • Preparation method and application of polycarbonate-based polymer electrolyte

    CN109802174A

  • Non-aqueous electrolyte secondary battery and its manufacturing method

    JP2004227967A

  • Composition for electrolyte, polymer electrolyte and battery using it

    JP2004311114A